Predicting Academic Success: A Longitudinal Study of University Design Students. - Crowther, Philip; Briant, Sarah (International Journal of Art & Design Education, 2021)
This article presents a longitudinal study, over eleven years, of the academic progress of a cohort of design students (n = 475) at a major Australian university. The students were from four different spatial design disciplines: architecture, industrial design, interior design, and landscape architecture. The article identifies cognitive variables that may predict future academic success. This research uses regression analysis to identify correlations across a range of variables, in particular exploring the relationship between university entrance scores, subjects studied at school (art and graphics) and academic success as defined by university grade point average and time to completion. This study shows that prior knowledge in art and graphics is not a useful predictor of future academic success, while university entrance scores and first year performance are related to ongoing academic success. These results suggest that for the design disciplines explored here, discipline‐specific prior knowledge is not an important requirement for university entrance.